HAPPINESS AND PSYCHOLOGICAL WELL-BEING IN THE RESOURCE MODEL STRUCTURE OF PSYCHOLOGICAL HEALTH - V. G. Petrov (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The article is dedicated to the problem of psychological health of the individual. The purpose of the article is analyzing the problem of psychological health from the standpoint resource approach. The authors propose a model of psychological health, which is based on the concepts of "psychological resources" and "personal potential". As part of the resource model, psychological health is considered instrumental resource (the potential of a possible) and effectively-activity (the potential achieved) aspects. The potential of a possibilities are defined as the balance between external (by environmental, historical and cultural) and internal (resources and constraints) conditions. The potential achieved is regarded as a four-hierarchical structure, which includes the following levels: 1) the level of deviations and violations of psychological health, 2) the level of standards, 3) the level of psychological well-being, 4) the level of existentially experienced happiness. This article is a part of the larger theoretical and empirical research.